2019
DOI: 10.2337/dc19-1651
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity and Renal Hemodynamic Function in Metformin-Treated Adults With Type 2 Diabetes and Preserved Renal Function

Abstract: Impaired insulin sensitivity is associated with hyperfiltration (i.e., elevated glomerular filtration rate [GFR]) in adolescents with type 2 diabetes (T2D) and adults with prediabetes. Yet, these relationships are based on studies that relied on estimated GFR (eGFR), estimates of insulin sensitivity, or both. We aimed to verify the relationship between insulin sensitivity and renal hemodynamic function by gold standard methods in adults with T2D. RESEARCH DESIGN AND METHODSInsulin sensitivity was assessed by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…Interestingly, in this study, subjects with prediabetes and HGFR exhibited a lower insulin sensitivity (expressed as Matsuda Index); furthermore, the study demonstrated a significant association between high eGFR and insulin resistance (expressed as HOMA index); in the kidney, insulin-resistance/sensitivity may act at multiple levels and modulate different functions such glomerular filtration, gluconeogenesis, renal sodium handling and others [31]. In agreement with our data, van Bommel et al recently demonstrated that impaired insulin sensitivity is associated with intrarenal hemodynamic dysfunction by gold standard techniques (hyperinsulinemiceeuglycemic clamp and urinary inulin) in adults with type 2 diabetes treated with metformin monotherapy [32]. The association between insulin resistance and cardiovascular disease has been previously reported, however, these results suggest that insulin resistance may be associated with hemodynamic renal dysfunction, including hyperfiltration, and raise the possibility that it may represent one factor linking renal function and cardiovascular disease [33].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, in this study, subjects with prediabetes and HGFR exhibited a lower insulin sensitivity (expressed as Matsuda Index); furthermore, the study demonstrated a significant association between high eGFR and insulin resistance (expressed as HOMA index); in the kidney, insulin-resistance/sensitivity may act at multiple levels and modulate different functions such glomerular filtration, gluconeogenesis, renal sodium handling and others [31]. In agreement with our data, van Bommel et al recently demonstrated that impaired insulin sensitivity is associated with intrarenal hemodynamic dysfunction by gold standard techniques (hyperinsulinemiceeuglycemic clamp and urinary inulin) in adults with type 2 diabetes treated with metformin monotherapy [32]. The association between insulin resistance and cardiovascular disease has been previously reported, however, these results suggest that insulin resistance may be associated with hemodynamic renal dysfunction, including hyperfiltration, and raise the possibility that it may represent one factor linking renal function and cardiovascular disease [33].…”
Section: Discussionsupporting
confidence: 91%
“…Sex hormones may directly affect renal function, for example, testosterone may induce glomerular podocyte apoptosis and activate the reninangiotensin system, whilst oestrogen may have opposite effects [4]. Correspondingly, fasting insulin is associated with renal haemodynamic function [40], is responsive to a highenergy diet [41] and regulates blood pressure possibly through the renin-angiotensin system [42], besides being a potential driver of growth and reproduction [7,8]. Nevertheless, our findings are consistent with differing disease patterns by person, place and time.…”
Section: Discussionmentioning
confidence: 99%
“…The annual rate of eGFR decline was reported to be greater in patients with type 2 DM than in those without DM [37]. Insulin resistance might be associated with intrarenal hemodynamic dysfunction and predictive of all-cause mortality in patients with type 2 DM [38,39]. Diabetic retinopathy was reported to be associated with eGFR variability and predictive of all-cause mortality in patients with type 2 DM [40,41].…”
Section: Discussionmentioning
confidence: 99%